Toward a Psychology of Social Change: A Typology of Social Change - de la Sablonnière, Roxane (Frontiers in Psychology, 2017)
Millions of people worldwide are affected by dramatic social change (DSC). While sociological theory aims to understand its precipitants, the psychological consequences remain poorly understood. A large-scale literature review pointed to the desperate need for a typology of social change that might guide theory and research towards a better understanding of the psychology of social change. Over 5000 abstracts from peer-reviewed articles were assessed from sociological and psychological publications. Based on stringent inclusion criteria, a final 315 articles were used to construct a novel, multi-level typology designed to conceptualize and categorize social change in terms of its psychological threat to psychological well-being. The typology of social change includes four social contexts: Stability, Inertia, Incremental Social Change and, finally, DSC. Four characteristics of DSC were further identified: the pace of social change, rupture to the social structure, rupture to the normative structure, and the level of threat to one’s cultural identity. A theoretical model that links the characteristics of social change together and with the social contexts is also suggested. The typology of social change as well as our theoretical proposition may serve as a foundation for future investigations and increase our understanding of the psychologically adaptive mechanisms used in the wake of DSC.